Meta-Analysis: The Effect of Acupuncture Therapy in Reducing Migraine Recurrence - Elsa Tursina; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Acupuncture therapy is an effective treatment for reducing headache intensity, migraine recurrence, and improving quality of life. This study aims to analyze and estimate the effect of acupuncture therapy on reducing migraine recurrence.Subjects and Method: This study used a systematic review and meta-analysis by following PICO, Population: migraine patients. Intervention: acupuncture therapy. Comparison: no acupuncture therapy. Result: reduction in migraine recurrence. The data used were obtained from scientific research articles from the Pubmed, Google Scholar, Science Direct, and SpringerLink electronic databases with a Randomized Control Trial (RCT) design from 2011 to 2022 which reports effect sizes with Mean and SD. The keywords used in the search for scientific articles are “Acupuncture” AND “Profilaxis Migraine” AND “Migraine Frequency”. The selection of articles was carried out using the PRISMA flowchart. Data were analyzed using Review Manager software version 5.4.1.Results: A total of 9 articles with qualified RCT designs from Asia, America, Australia, and Europe were selected for the systematic review and meta-analysis. The results of the meta-analysis showed that patients with migraine who received acupuncture therapy experienced migraine recurrence 0.31 units lower than those who were not treated with acupuncture (SMD= -0.31; 95% CI= -0.61 to -0.01; p=0.040).Conclusion: Acupuncture therapy reduces migraine recurrence.Keywords: acupuncture, relapse, migraine.Correspondence: Elsa Tursina. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: elsa090798@gmail.com. Mobile: +6285655751077.Indonesian Journal of Medicine (2023), 08(01): 47-58https://doi.org/10.26911/theijmed.2023.08.01.05